The relationship between childhood trauma and psychological resilience - Yılmaz Bingöl, Tülay; Özkök, Zeynep; Gürhan, Nermin (Nursing and Health Sciences Journal (NHSJ), 2025)
Childhood traumas include physical abuse, emotional abuse, sexual abuse, physical neglect, and emotional neglect. The impact of childhood traumas on psychological resilience is emphasized. This study aims to examine the effects of childhood traumas on the psychological resilience of individuals. The study was conducted as a descriptive and quantitative study. The study was conducted online between 08.11.2021 and 10.20.2021 with the utilization of the snowball sampling method (322 women, 92 men, total: 414 participants) and with the participants over the age of 18 who agreed to participate in the study. The Personal Information Form, Adult Resilience Measure (ARM), and Childhood Trauma Questionnaire-33 (CTQ-33) were used as data collection tools. It was determined that the mean score of the participants' Childhood Trauma Questionnaire-33 was 48.45±11.68, and its subscales' mean scores were 8.24±3.86 for emotional abuse, 6.15±2.31 for physical abuse, 7.97±2.56 for physical neglect, 9.29±2.39 for emotional neglect, 6.01±2.71 for sexual abuse, and 10.77±3.90 for overprotection-overcontrol. Additionally, the mean score of denial was determined to be 0.40±0.66. It was determined that the mean score of the Adult Resilience Measure was 81.73±13.59. In general, we can say that the negative experiences experienced by children negatively affect their future lives in the long term.